Pengaruh Karakteristik Dewan Pengawas Syari’ah dan Ukuran Dewan Komisaris terhadap Pengungkapan Islamic Social Reporting - Firman Setiawan (Al Maal: Journal of Islamic Economics and Banking, 2020)
This study aims to determine the effect of Shari'ah Supervisory Board Characteristics (DPS Size, DPS Education Level, and DPS Expertise) and Board of Commissioners Size on Islamic Social Reporting (ISR) Disclosure at Shari'ah Commercial Banks in 2018. Population in this study is a Sharia Commercial Bank in Indonesia in 2018. Data is obtained from the bank's annual report. The data is presented and analyzed quantitatively using multiple linear regression. Based on the analysis conducted, it is known that the Shari'ah Supervisory Board Size, Shari'ah Supervisory Board Education Level and the Shari'ah Supervisory Board Expertise partially have no significant effect on Islamic Social Reporting (ISR) Disclosure, while the Size of the Board of Commissioners has a significant effect on Islamic Social Reporting (ISR) Disclosures. Simultaneously, DPS Characteristics and Board of Commissioners Size significantly influence Islamic Social Reporting (ISR) Disclosure.